Franz Kafka, Paul Auster and the end of the American century - Šesnić, Jelena (2012)
My reading will evolve within the purview of the argument that the 20th century was the American century, whereas the 21st century witnesses the demise of the American hegemony on the global scale or at least brings in some other major players. Consequently, Franz Kafka's early twentieth-century novel, Amerika (1927), left unfinished upon his death, will serve as a starting point of my analysis, while the end point of the trajectory of the American role in the preceding decades will be marked by Paul Auster's most recent novel Sunset Park (2010). My argument will try to show how literature registers some seismic shifts in the discourses of America, both from the outside and on the inside, and how literature in particular reflects key moments in the national self-making and (self)-definition. Appropriate models of historical, political and cultural provenance will be used as examples of the changing descriptions of the nation and the way it conceptualizes its status among other world nations in terms of a certain mythology (for instance, from progress to decadence ; the march of civilization ; Manifest Destiny).